Leveraging Ice, Cloud, and Land Elevation Satellite-2 Laser Altimetry and Surface Water Ocean Topography Radar Altimetry for Error Diagnosis in Hydraulic Models: A Case Study of the Chao Phraya River - Theerapol Charoensuk; Jakob Luchner; Peter Bauer-Gottwein (Remote Sensing)
Recent advancements in satellite Earth observation (EO) technology have significantly improved the accuracy and density of data available for monitoring rivers and streams, as well as for diagnosing errors in hydraulic models. Laser and radar altimetry missions, such as ICESat-2 (Ice, Cloud, and Land Elevation Satellite-2) and SWOT (Surface Water and Ocean Topography), offer high-resolution measurements of land and water surface elevation (WSE), covering entire river reaches and providing high-resolution WSE profiles along the river chainage, which can be directly compared to hydraulic model results. In this study, we implemented a workflow to assess the accuracy of simulated WSE and evaluate the performance of hydraulic models in the Chao Phraya (CPY) River, using WSE data from ICESat-2 and SWOT. The evaluation of ICESat-2, SWOT, and simulated WSE from the model, compared to in situ data, resulted in root mean square error (RMSE) values of 0.34 m, 0.35 m, and 0.37 m, respectively. Despite this, both ICESat-2 and SWOT data proved effective for error detection and performance evaluation along the CPY river in point, profile, and spatial map comparisons, with overall RMSE values of 0.36 m and 0.33 m, respectively, when compared with simulated WSE. This paper demonstrates that ICESat-2 and SWOT are valuable tools for diagnosing errors and improving hydraulic model performance, providing critical insights for river monitoring and model validation.